2022
DOI: 10.3390/buildings12020181
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of a Low-Income Building: A BIM-LCSA-FAHP-Based Analysis

Abstract: The construction industry is one of the most significant consumers of environmental resources worldwide. Faced with the need to produce new buildings, but without further burdening the environment, attempts to improve social, economic, and environmental indicators have turned attention to building construction in recent decades. The objective of this research is to develop a novel framework to assess the most sustainable choice of materials applied to the construction of low-income buildings, according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Based on the conducted review, a strategic selection of sustainable KPIs can align construction practices more closely with global sustainability goals and frameworks [31]. Systems focused on O-SCP, as concluded by [47], offer numerous benefits, such as pollution control and optimized resource allocation [48,49]. These systems also foster improved compliance with regulations, risk assessment, and proactive problem prevention [26].…”
Section: Sustainability Dimensions and Kpismentioning
confidence: 99%
“…Based on the conducted review, a strategic selection of sustainable KPIs can align construction practices more closely with global sustainability goals and frameworks [31]. Systems focused on O-SCP, as concluded by [47], offer numerous benefits, such as pollution control and optimized resource allocation [48,49]. These systems also foster improved compliance with regulations, risk assessment, and proactive problem prevention [26].…”
Section: Sustainability Dimensions and Kpismentioning
confidence: 99%
“…The assessment included different impact parameters, i.e., global warming, abiotic depletion, acidification, etc. In a similar study, Filho, da Costa [39] used BIM in the context of Life Cycle Sustainability Assessment comprising socio-economic and environmental aspects. A study by Peng [40] contended that the estimation of carbon emissions over a building's life cycle can be simplified by BIM and Ecotect as they can supply most of the relevant information required for LCA calculations.…”
Section: Bimmentioning
confidence: 99%
“…For such assessment, the energy efficiency label is potential solution widely praised for its simple and intuitive structure, easy-to-understand, small investment, and obvious benefits. Studies have shown that public buildings consume a great amount of energy during the entire life cycle, so their energy efficiency has received extensive attention from many researchers [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%